2021
DOI: 10.1186/s40644-021-00384-9
|View full text |Cite|
|
Sign up to set email alerts
|

Diffusion-weighted MRI improves response assessment after definitive radiotherapy in patients with NSCLC

Abstract: Background Computed tomography (CT) is the standard procedure for follow-up of non-small-cell lung cancer (NSCLC) after radiochemotherapy. CT has difficulties differentiating between tumor, atelectasis and radiation induced lung toxicity (RILT). Diffusion-weighted imaging (DWI) may enable a more accurate detection of vital tumor tissue. The aim of this study was to determine the diagnostic value of MRI versus CT in the follow-up of NSCLC. Methods T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Importantly, online MRgRT enables real-time tumour monitoring during treatment and motion management by means of gating/tracking strategies thus eliminating the need for larger margins or internal target volume (ITV) concepts to account for tumour mobility. To further unlock new capabilities of this novel technology, functional imaging including diffusion-weighted imaging facilitates response assessment during and after primary treatment [ 12 ]. Therefore, promoting adaptive and dose-escalation strategies based on biological response similar to concepts employed with PET imaging [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, online MRgRT enables real-time tumour monitoring during treatment and motion management by means of gating/tracking strategies thus eliminating the need for larger margins or internal target volume (ITV) concepts to account for tumour mobility. To further unlock new capabilities of this novel technology, functional imaging including diffusion-weighted imaging facilitates response assessment during and after primary treatment [ 12 ]. Therefore, promoting adaptive and dose-escalation strategies based on biological response similar to concepts employed with PET imaging [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…22 The continuous technical development in MRI with fast imaging techniques, resulting in protocols with scan times between 15 and 30 minutes, 23 has made chest MRI an interesting alternative to CT. 19,24 In addition, MRI can provide additional functional sequences compared to CT, especially DWI. From the latest research, tumor volume measurement can be done by DWI yielding similar results to CT. 25 Only a few studies have explored the preoperative differentiation of NSCLC histological grades based on dual-energy CT and ADC in recent years. 9,26 These tests have limitations, including CT ionizing radiation problems and overlap of ADC values.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MRI can provide additional functional sequences compared to CT, especially DWI. From the latest research, tumor volume measurement can be done by DWI yielding similar results to CT 25 . Only a few studies have explored the preoperative differentiation of NSCLC histological grades based on dual‐energy CT and ADC in recent years 9,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, a very small number of patients cannot complete an MRI examination due to claustrophobic syndrome or ferromagnetic objects in the body that cannot be removed. At present, it has been stated that DW-MRI plays an equivalent role to CT in detecting tumor volume in NSCLC patients after chemotherapy and can even reliably determine the range of radiation-induced lung toxicity [ 26 ]. Gkogkozotou et al [ 22 ] have found that the combination of PET/CT and brain MRI is beneficial to accurately classifying the stages of NSCLC and reduce avoidable thoracotomy.…”
Section: Discussionmentioning
confidence: 99%